431 An Observational Analysis of Randomized Controlled Trials (RCTs) Discontinuation and Non-Publication in Spine Disease. (April 2023) - Tiefenbach, Jakov; Demetriades, Andreas K.; Park, Jay
Abstract : INTRODUCTION: Incompleteness and non-publication of Randomized Controlled Trials (RCTs) have been increasingly reported in the literature. This is a significant concern as RCTs demand monumental amounts of healthcare resources leading to wastage. Most importantly, both under-reporting and non-publication distorts evidence landscape and obscures rationale behind clinical decisions. METHODS: A list of RCTs was obtained from the U.S National Library of Medicine ClinicalTrials.gov database from January 1st, 2013, to December 31st, 2020. Two independent authors excluded all non-RCTs, trials unrelated to spinal diseases, and trials that are in or before the recruitment phase. We extracted the progress status, sources of funding, number of centers, type of intervention, principal investigator's department affiliation, publication status, location, reason for discontinuation, publication date, and subtopics. RESULTS: A total of 112 trials were included in the study. Twenty-five (22%) trials were discontinued early, with slow recruitment being the major reason (38%). Only fifty-six (50%) of the trials were published in peer-reviewed journals. Trial discontinuation was much higher in trials registered in the United States (US) compared to other countries (P = 0.009). There were 11 (23.4%) industry-sponsored and 14 (21.5%) non-industry-sponsored studies that remained uncompleted. Over the study period, only 20% of the trials were fully compliant with the FDA reporting requirements. CONCLUSIONS: Nearly a quarter of all trials in spinal disorders were discontinued. Half of the trials were unpublished. These rates remain worrisome from an ethical and financial perspective. Both under-reporting and non-publication adversely affect patient safety and waste valuable healthcare resources. An organized effort is needed to address this important issue and improve the rates of trial completion and publication.